2017
DOI: 10.18632/oncotarget.14618
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase antagonist imetelstat increases radiation sensitivity in esophageal squamous cell carcinoma

Abstract: The morbidity and mortality of esophageal cancer is one of the highest around the world and the principal therapeutic method is radiation. Thus, searching for sensitizers with lower toxicity and higher efficiency to improve the efficacy of radiation therapy is critical essential. Our research group has previously reported that imetelstat, the thio-phosphoramidate oligonucleotide inhibitor of telomerase, can decrease cell proliferation and colony formation ability as well as increase DNA breaks induced by radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…A change in mesenchymal stem cell morphology, loss of adhesion, and G1 phase arrest of the cell cycle have been demonstrated (99). Although the use of GRN163L alone is currently ineffective, it has been shown to have promising effects in combination with other molecularly targeted drugs or in the sensitization of cancer cells to radiation therapy (100)(101)(102). T-oligos homologous to the 3'-telomeric overhang are also promising oligonucleotides that have demonstrated anticancer activity.…”
Section: Telomeres As a Possible Therapeutic Targetmentioning
confidence: 99%
“…A change in mesenchymal stem cell morphology, loss of adhesion, and G1 phase arrest of the cell cycle have been demonstrated (99). Although the use of GRN163L alone is currently ineffective, it has been shown to have promising effects in combination with other molecularly targeted drugs or in the sensitization of cancer cells to radiation therapy (100)(101)(102). T-oligos homologous to the 3'-telomeric overhang are also promising oligonucleotides that have demonstrated anticancer activity.…”
Section: Telomeres As a Possible Therapeutic Targetmentioning
confidence: 99%
“…In vivo, treatment with GRN163L decreased tumor volume in a mouse xenograft model [80]. Additionally, GRN163L increased radiation sensitivity in esophageal squamous cell carcinoma cell lines, leading to increased apoptosis [81,82]. Although these studies suggest promise for a potential GI cancer therapeutic, to date, 19 clinical trials have been opened utilizing GRN163L, yet none have been targeted at GI cancers [83].…”
Section: Antitelomerase Therapymentioning
confidence: 99%
“…One study using esophageal cancer cells showed that cells treated with GRN163L underwent significantly higher levels of apoptosis than untreated cells after undergoing radiation therapy. Additionally, mouse esophageal cancer xenografts showed enhanced apoptosis and inhibition of proliferation following radiation treatment combined with GRN163L [ 31 ]. Another study in mouse orthotopic glioblastoma xenograft models also showed that after treatment with 30 mg/kg of GRN163L triweekly for a month followed by five days of radiation therapy, mice had an increased overall survival compared to those treated with radiation or GRN163L alone.…”
Section: Grn163lmentioning
confidence: 99%